Flexural behaviour of partially bonded carbon fibre reinforced polymers strengthened concrete beams: Application to fire protection systems design. (January 2015) - Firmo, J.P.; Arruda, M.R.T.; Correia, J.R.; Tiago, C.
Highlights: The mechanical behaviour of partially bonded CFRP strengthened beams was modelled. Two dimensional non-linear finite element models were developed. Partially bonded beams can present similar flexural strength to fully bonded ones. Relations between the bonded length and the strength reduction were proposed. The proposed relations were used for the design of fire protection systems. Abstract: Recent fire resistance tests on reinforced concrete (RC) beams strengthened with carbon fibre reinforced polymers (CFRP) laminates showed that it is possible to attain considerable fire endurance provided that thermal insulation is applied at the anchorage zones of the strengthening system. With such protection, although the CFRP laminate prematurely debonds in the central part of the beam, it transforms into a cable fixed at the extremities until one of the anchorage zones loses its bond strength. The main objective of this paper is to propose a simplified methodology for the design of fire protection systems for CFRP strengthened-RC beams, which is based on applying thicker insulation at the anchorage zones (promoting the above mentioned "cable behaviour") and a thinner one at the current zone (avoiding tensile rupture of the carbon fibres). As a first step towards the validation of this methodology, finite element (FE) models were developed to simulate the flexural behaviour at ambient temperature of full-scale RC beams strengthened with CFRP laminates according to the externally bonded reinforcement (EBR) and near surface mounted (NSM) techniques, in both cases fully or partially bonded (the latter simulating the cable). The FE models were calibrated with results of 4-point bending tests on small-scale beams and then extended for different beam geometries, with spans ( L ) varying from 2 m to 5 m, in which the influence of the CFRP bonded length ( lb ) and the loading type (point or uniformly distributed) on the strength reduction was evaluated. The results obtained show that the strength reduction decreases when the ratio lb / L increases; the loading type does not present a relevant influence on the strength reduction; and, for similar lb / L ratios, the strength reduction suffered by NSM-strengthened beams is lower than that of EBR-strengthened beams. Relations between the strength reduction due to the partial bonding and the lb / L ratio were defined for both loading cases and strengthening techniques. These results, obtained at ambient temperature, were then incorporated in a simplified procedure that is proposed for the design of fire protection systems of CFRP-strengthened RC flexural members.